Ossification: a new approach to immobilize metal complex catalysts - applications to carbonylation and Suzuki coupling reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Journal of Catalysis, 2006)
A simple approach for immobilization of transition metal complexes is reported here based on the transformation of the complex into its intrinsically insoluble counterpart, thus generating solid molecular catalysts. This approach that we call ``ossification'' is based on a principle, in which the water-soluble analogues of the metal complexes are precipitated out from aqueous solutions as insoluble ionic ensembles having catalytically active metal-centered coordination environments and robust framework. The approach has been illustrated for I'd complex catalyzed carbonylation and Suzuki coupling reactions. ``Ossification'' was found to be an economically and environmentally attractive alternative to other exotic immobilization methodologies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Carbonylation; Heterogeneous catalysts; Immobilization; ossification; Palladium complex; Suzuki coupling

Correlating the role of hydrophilic/hydrophobic nature of Rh(I) and Ru(II) supported organosilica/silica catalysts in organotransformation reactions - Lazar, Anish; George, Shoy C.; Jithesh, P. R.; Vinod, C. P.; Singh, A. P. (Applied Catalysis A-General, 2016)
Highly reactive and hydrophobic triphenyl phosphine based rhodium(I) and ruthenium(II) organometallic complexes over benzene containing periodic mesoporous organosilica (PMOB) have been synthesized. This has been achieved by the immobilization of neat metal complexes like RhCl(PPh3)(3) [Wilkinson catalyst], RuHCl(CO)(PPh3)(3) and RuCl2(PPh3)(3) over aminofunctionalized PMOB to get RhCl(PPh3)(2)-PrNH2PMOB, RuHCl(CO)(PPh3)(2)-PrNH2PMOB and RuCl2(PPh3)(3)-PrNH2PMOB, respectively. The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption analyses, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, SEM, TEM and contact angle measurements. The XRD and N-2 sorption analyses showed excellent textural properties with ordered mesoporous channel structure of all synthesized catalysts. The organic moieties anchored in PMOB were confirmed by C-13 CPMAS NMR and Fr-IR spectroscopy with Si-29 CPMAS NMR spectroscopy providing the information about the degree of functionalization of surface silanol groups with organic moiety. The Rh(I) and Ru(II) complexes supported on MCM-41/SBA-15/PMOE (ethane-PMO) were synthesized, and their catalytic activities in hydrogenation and sulfoxidation reactions were compared with Rh(I) and Ru(II) complexes supported on PMOB. The results show that PMOB based catalysts exhibit higher activities and selectivities than MCM-41/SBA-15/PMOB supported catalysts, neat homogeneous complexes and without catalyst. The better catalytic performance of PMOB based catalyst is attributed to the hydrophobic nature and high surface area of the PMOB support. The recycling studies of anchored catalysts show no major deactivation of the catalyst. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Hydrogenation and sulfoxidation; Hydrophobic; Periodic mesoporous organosilica

Multifunctional nanocatalysts for tandem reactions: a leap toward sustainability - Jagadeesan, Dinesh (Applied Catalysis A-General, 2016)
Design of new multifunctional nanocatalysts is a hot area of research that aims to introduce multiple types of active sites on a single nanocatalyst. Multifunctional nanocatalysts are useful to carry out a multi-step reaction requiring same or different active sites in a single pot. Such catalysts must possess the active sites at spatially distinct locations to avoid neutralization but yet remain active independently or through cooperative actions. The necessity of nanostructuring the active sites have emerged as the key point in a successful design of the catalysts. The review covers the progress in this area of research done in the last five years. It includes the classification of catalysts based on active sites and structure of active sites at the nanoscale. The review covers exhaustively with 250+ references and ample examples to present the concept succinctly. The review covers the evolution of multifunctional catalysts from the perspective of materials chemistry. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heterogeneous catalysts; Multifunctional nanocatalysts; Nanostructured materials; Tandem reactions

Review on selective production of acetophenone from oxidation of ethylbenzene over heterogeneous catalysts in a decade - Nandanwar, Sachin U.; Rathod, Simmy; Bansal, Videsha; Bokade, Vijay V. (Catalysis Letters, 2021)
The consumption of acetophenone (AP) is increasing worldwide because of its applications in products such as alcohol, aldehydes, resins, esters, fragrances, and pharmaceuticals. AP is manufactured via several methods like decomposition of cumene hydroperoxide, Hock process, and Friedel-Crafts acylation reaction using homogeneous catalysts with solvent and oxidant. However, it causes several environmental problems that deteriorate the production of AP with these methods. Oxidation of ethylbenzene (EB) is one of the promising methods to synthesize AP in liquid and vapor phases reaction using heterogeneous catalysts, which plays a vital role for selective production of AP. In this review, numerous heterogeneous catalysts are discussed including transition metal nanoparticles, transition metal complexes, and metal free catalysts (carbon nanotubes) used in last 10 years for oxidation of EB. Additionally, catalyst activity along with reaction parameters and its effect, mechanisms, and kinetics study are summarized in this article. The future scope of this reaction is also highlighted. Moreover, this work identifies best catalysts for bulk production of AP with high yield to satisfy global requirement.
Keywords: acetophenone; ethylbenzene; Heterogeneous catalysts; Oxidation reaction; reaction mechanisms

Green synthesis of highly dispersed Cu metal nanoparticles catalysts - Nagpure, Atul S.; Mohture, Vikas M.; Kayarkar, Ankush (Inorganic Chemistry Communications, 2022)
Bionanotechnology approach for metal nanoparticles (NPs) synthesis is cost-effective and environmentally friendly. Organic molecules present in plant extracts can be efficiently utilized for bio-reduction of metal ions into metal NPs in a one-step green synthesis methodology. The biosynthesis procedure for metal NPs synthesis is quick, easy to scale up and can be perform at ambient conditions. The present investigations propose the biosynthesis of highly dispersed and stable copper NPs (Cu NPs) supported on NaY zeolite using plant extract of Tinospora cordifolia and Andrographis paniculata for the first time. The structural and morphological attributes of Cu NPs were explored by adopting various physico-chemical techniques, for example Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES), X-ray diffraction (XRD), Temperature Programmed Desorption (CO2-TPD and NH3-TPD), Temperature Programmed Reduction (H2-TPR), N2 sorption, Electron Microscopy (SEM, TEM and HR-TEM), X-ray Photoelectron Spectroscopy (XPS), etc. The experimental study (XRD, SEM, TEM, and HR-TEM) recommend that the green synthesis method by using plant extract has promising effect for the synthesis of nano-sized, stable and homogeneously dispersed Cu NPs catalysts (Cu NPs average size of 1.6 and 1.8 nm) as compared to chemical synthesis approach. The present result is better than those of many state-ofthe art techniques reported for green synthesis of Cu NPs using plant extract. According to the current study, it is advantageous to prepare highly dispersed metal NPs with desired size, shape, morphology and the required properties by using plant extract.
Keywords: Biosynthesis of nanomaterials; Cu nanoparticles; Heterogeneous catalysts; Support -Metal interaction; Zeolite supported catalysts